THE IMPACT OF DISTORTED HISTORICAL INFORMATION IN TIKTOK VIDEOS ON STUDENTS' UNDERSTANDING OF HISTORY (Naturalistic Inquiry Study in Class XI SMAN 1 Garut) - Hadianto Harisma; Agus Mulyana; Wildan Insan Fauzi (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
Abstract in Historical distortions in social media content, particularly on TikTok, pose a new challenge in history education because the information disseminated is often simplistic, provocative, and lacking in historiographical accuracy. This study was motivated by the phenomenon of widespread historical content on TikTok that does not align with historical facts yet remains popular and trusted by students. The objective of this study is to examine the impact of historical distortion in TikTok content on students' understanding of history at SMA Negeri 1 Garut. The method used is qualitative with a naturalistic inquiry approach, focusing on in-depth interviews with students and history teachers, participatory observation, and document analysis of the historical content consumed by students. The results of the study indicate that most students are influenced by invalid historical content on TikTok, which leads to misinterpretations of historical events, weak critical thinking skills regarding sources, and the emergence of narrow and biased historical perceptions. On the other hand, teachers play a crucial role in countering such distortions through educational approaches that emphasize source clarification, open discussions, and media literacy enhancement. The conclusion of this study emphasizes that history education in the digital age must be accompanied by adaptive and critical pedagogical strategies, so that students can distinguish between valid and distorted historical narratives and grow into active subjects in building reflective and responsible historical understanding.